An economically viable method for the removal of cobalt ions from aqueous solution using raw and modified rice straw - A.A. Swelam; M.B. Awad; A.M.A. Salem; A.S. El-Feky (HBRC Journal, 2018)
Cobalt contamination in wastewater from industries has been increased in many countries including Egypt. Adsorption is the most progressively for heavy metals, removing from wastewater by using agricultural waste and by-products such as rice straw. Unmodified and modified rice straw has been evaluated as their ability to bind with metal ions. In this study, four characterizations of raw rice straw have been conducted. The morphological characteristics by SEM, EDXA, and the functional group present in the rice straw by FTIR spectroscopy and the XRD technique. Rice straw contains about OH functional group that can bind with metal ions. To be able to enhance the sorption capacity of rice straw in metals, removing from waste water, alkali treatment should be done. This shows that rice straw can be used as adsorbent for removing cobalt ions from wastewater. The effect of pH, amount of adsorbent, different concentrations of cobalt, sorption kinetics and isotherms were studied in batch experiments. The good correlation coefficient was obtained from pseudo second-order kinetic model, which agreed with conception as the rate-limiting mechanism. Sorption isotherm test showed that equilibrium sorption data were better represented by Langmuir model than the Freundlich model. The thermodynamic parameters such as ΔH, ΔS, ΔG and Ea are also calculated. Keywords: Rice straw, Adsorption, Cobalt, Kinetic, Thermodynamic